A systematic review of occupational exposure to coal dust and the risk of interstitial lung diseases. Issue 1 (1st January 2017) - Beer, Christiane; Kolstad, Henrik A.; Søndergaard, Klaus; Bendstrup, Elisabeth; Heederik, Dick; Olsen, Karen E.; Omland, Øyvind; Petsonk, Edward; Sigsgaard, Torben; Sherson, David L.; Schlünssen, Vivi
ABSTRACT: Objective : Exposure to coal dust can cause interstitial lung disease (ILD), but whether this is due to pure coal or to the contents of quartz in coal is less clear. Here, we systematically reviewed the relation between 'pure coal' and ILD. Methods : In a systematic review based on PRISMA criteria 2945 articles were identified. Strict eligibility criteria, which evaluated the 'pure coal effect', led to the inclusion of only nine studies. Results : Among these nine studies six studies indicated an independent effect of the non-quartz part of coal on the development and progression of ILD, two did not demonstrate an effect and one was inconclusive. Conclusions : Although an independent effect of non-quartz coal dust on the development of ILD is supported, due to methodological limitations the evidence is limited and further evidence is needed.